CARBON TAX AS AN IMPLEMENTATION OF THE POLLUTER PAYS PRINCIPLE IN INDONESIA - Febiola, Stefany; Edbert, Felicia; Ariffin, Melissa; Sanjaya, Ronaldo (Sabtida, 2023)
Climate issues are a growing concern that governments around the world recognize need to be addressed. Climate change and its devastation are being felt around the world. Especially the issue of greenhouse gas emissions in 2015. This study aims to analyze a comparison of the implementation of the Polluter Pays Principle as an effort to implement carbon taxes in Indonesia. This type of research is descriptive qualitative normative. The specification of this research is analytical descriptive. With regard to the impact of climate change that has become a global challenge that needs to be handled together, the government is therefore seeking various ways and systems to achieve the GHG emission reduction target in the medium to long term. The government must carefully prepare the collection system, tax base, and rates for the correct use of earnings. Implementation must also be supported by simple administration, clear rules and effective outreach.